EFEKTIFITAS INTERVENSI TERAPI MUSIK KLASIK TERHADAP STRESS DALAM MENYUSUN KARYA TULIS ILMIAH (KTI) MAHASISWA AKADEMI KESEHATAN SAPTA BAKTI BENGKULU - Nengke Puspita Sari; Sutri Yani (Jurnal Sains Kesehatan, 2017)
Stress is a condition of physical and psychological stress due to the demands of the self and the environment. The many demands of the task and the scientific paper is a stressor that can cause stress for students. One method to overcome the stress that is with music therapy. This study aimed to determine differences in stress levels before and after music therapy at the final stage of a student who made scientific paper at Sapta Bakti Health Academy Bengkulu. The sampling technique in this study was Purposive Sampling with the number of respondents 31 people. This type of study was pre-experiment which belong to the pre-test and post-test one group design. Analysis of statistical data used was the Wilcoxon Match Pairs Test. The data was collected at the time before and after therapy was given to classical music by using the DASS 42 Instrument developed by Lovibond and Lovibond was used as a stress gauge items. Based on this research, there were differences in stress levels of respondents before and after the therapy was given to classical music. From the results of Wilcoxon test for levels of stress before and after therapy to classical music both obtained significance value of 0.000 which was smaller than α = 0.05. The difference could be seen was the decline in the number of respondents prior to the classical music therapy on stress levels of students was 8 people students (26%) experienced severe stress, 8 students (26%) experienced mild stress, and 15 students (48%) experienced stress is. Meanwhile, after the classical music therapy decreased stress levels, as many as 2 students (7%) experienced mild stress, 11 were students (35%) became normal, 8 students (26%) experienced mild stress and 10 students (32% ) are stressed. Based on this research was expected to provide inputs to the nurses and educational institutions, and other research so that it can cope with stress in college students. Keywords: classical music therapy, stress levels, scientific paper